2002
DOI: 10.1055/s-2002-36157
|View full text |Cite
|
Sign up to set email alerts
|

Koloskopie und Sigmoidoskopie bei über achtzigjährigen Patienten

Abstract: Endoscopy of the lower gastrointestinal tract is feasible in geriatric patients with a low rate of complications. The low number of normal findings and the frequent diagnosis of colorectal carcinoma were remarkable. In spite of old age more than half of the patients with carcinoma could be operated curatively emphasizing the importance of endoscopic investigations in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Similar to Cha et al, 9 we found that increasing age alters the indications for colonoscopy because nonagenarians were more likely to undergo colonoscopy due to rectal bleeding, anemia, and following an episode of volvulus, and less likely for polyp surveillance. As opposed to other studies, 12 we found that most of the nonagenarians were successfully and safely sedated and had a low procedurerelated complication rate. Nonagenarians were more likely to be sedated by fentanyl and propofol, to receive general anesthesia, and altogether needed lower medication doses compared with octogenarians.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to Cha et al, 9 we found that increasing age alters the indications for colonoscopy because nonagenarians were more likely to undergo colonoscopy due to rectal bleeding, anemia, and following an episode of volvulus, and less likely for polyp surveillance. As opposed to other studies, 12 we found that most of the nonagenarians were successfully and safely sedated and had a low procedurerelated complication rate. Nonagenarians were more likely to be sedated by fentanyl and propofol, to receive general anesthesia, and altogether needed lower medication doses compared with octogenarians.…”
Section: Discussioncontrasting
confidence: 99%
“…Realization of a colonoscopy is the principal diagnostic test and in many cases is also the main important therapy in this group of patients [6]. Although this procedure is safe, it generally only shows known and expected findings, especially in old patients [7].…”
Section: Introductionmentioning
confidence: 99%